THE CREDIBILITY OF LISTENING LEARNING VIDEOS FOR ELEMENTARY SCHOOL STUDENTS - Ardinata, Kadek; Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2021)
The limitations of appropriate learning media in online learning make listening skills difficult to teach. The purpose of this study is to develop listening learning videos for first-grade elementary students. This research is development research using ADDIE model, analysis, design, development, implementation, and evaluation. However, due to the pandemic situation, this research is only carried out until the development stage. The subjects in this study were two media experts, two material experts, and two practitioners. The method of data collection used in this study is the questionnaire method. The validity of the learning video is measured using the instrument rating scale in the form of an assessment sheet. Data analysis techniques use qualitative descriptive analysis and quantitative descriptive analysis. This study produced a listening learning video for first-grade elementary school students. The average validation score obtained in the listening learning video is 4.71, and the average material validation score is 4.81, with excellent criteria. Based on the study results, listening learning videos are declared valid and can be used in learning.